Students’ Tripartite Efficacy Beliefs in High School Physical Education: Within-and Cross-Domain Relations With Motivational Processes and Leisure-Time Physical Activity - Jackson, Ben; Whipp, Peter; Chua, Peter; Dimmock, J; Hagger, Martin (Human Kinetics, 2013)
Within instructional settings, individuals form relational efficacy appraisals that complement their self-efficacy beliefs. In high school physical education (PE), for instance, students develop a level of confidence in their teacher’s capabilities, as well as estimating how confident they think their teacher is in their (i.e., the students’) ability. Grounded in existing transcontextual work, we examined the motivational pathways through which students’ relational efficacy and self-efficacy beliefs in PE were predictive of their leisure-time physical activity. Singaporean students (N = 990; age M = 13.95, SD = 1.02) completed instruments assessing efficacy beliefs, perceptions of teacher relatedness support, and autonomous motivation toward PE, and 2 weeks later they reported their motivation toward, and engagement in, leisure-time physical activity. Structural equation modeling revealed that students reported stronger other-efficacy and RISE beliefs when they felt that their teacher created a highly relatedness-supportive environment. In turn, their relational efficacy beliefs (a) supported their confidence in their own ability, (b) directly and indirectly predicted more autonomous motives for participation in PE, and (c) displayed prospective transcontextual effects in relation to leisure-time variables. By emphasizing the adaptive motivational effects associated with the tripartite constructs, these findings highlight novel pathways linking students’ efficacy perceptions with leisure-time outcomes.